(untitled) (Revista LIDER, 2021)
This article addresses the issue of socio-territorial inequality in Zapopan using statistical techniques and spatial models for territorial analysis. The study of urban context through socio-economic indicators has allowed to understand the population dynamics, disclosing the factors that favor development as those who promote them. Social inequality, the economic situation of the population and their living conditions, are discussed as processes involved directly in the fragmentation of the urban landscape. In addition, the contrast between the sectoral structure of the workforce and its productive aptitude assess the socioeconomic level in different parts of the city. In this sense, the demographic conditions that influence the quality of life -determining the social polarization as well as the differentiation of the space- are identified.